2016
DOI: 10.1002/jsfa.8068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a diet containing dried grape pomace on blood metabolites and milk composition of dairy cows

Abstract: Inclusion of 15% GP in the diets of dairy cows is beneficial for overall normal blood constituent metabolism and helps to maintain cow health. The milk of cows fed with a GP diet preserves the normal levels of fat, protein and caseins, and has increased levels of components that make this milk a versatile ingredient material for the food industry (e.g. model whey powders, stability of lactose-rich powders). © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
(68 reference statements)
9
43
1
1
Order By: Relevance
“…Moreover, different concentrations (50, 75 and 100 g/kg of DM) of grape residue silage did not affect milk production nor the concentrations of CP, fat or lactose in dairy cows throughout a 21 days experimental period [10]. Further, the milk of dairy cows fed for three months with a diet containing 15% GP preserved the normal levels of fat, protein and caseins [22]. Finally, in a 4-week trial, dietary grape marc did not affect milk yield, milk protein or milk fat content of mid-lactation Holstein cows [40].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, different concentrations (50, 75 and 100 g/kg of DM) of grape residue silage did not affect milk production nor the concentrations of CP, fat or lactose in dairy cows throughout a 21 days experimental period [10]. Further, the milk of dairy cows fed for three months with a diet containing 15% GP preserved the normal levels of fat, protein and caseins [22]. Finally, in a 4-week trial, dietary grape marc did not affect milk yield, milk protein or milk fat content of mid-lactation Holstein cows [40].…”
Section: Discussionmentioning
confidence: 85%
“…Further, GP altered the nitrogen metabolism and decreased the ruminal ammonia production in male sheep [16], was shown to modify the rumen microbial population involved in methane metabolism [17], enhance the growth of facultative probiotic bacteria and inhibit the growth of pathogenic ones in lambs [18], but had no effect on milk yield and composition of dairy ewes [19]. In dairy cows, few studies, with varying results, have investigated the effects of GP dietary inclusion on milk production, composition and total polyphenols content as well as on the overall performance of animals [10,[20][21][22][23]. We have previously described the transcriptomic signature of veal calves fed with a GP-supplemented diet [24].…”
Section: Introductionmentioning
confidence: 99%
“…The high nutrient contents of the by-products make them for proper valorization, bringing both ecological and economic benefits (Helbig Table 4. Effects of berry seed residues on VFA concentrations in rumen fluid incubated in a batch culture system (experiment 1) Chedea et al, 2017). One of the methods allowing reuse of residues is their application in animal feed industries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pomace decreases the stress (oxidative) of lambs caused by the pen‐raising condition. Other studies reported that dietary replacement of cereal with grape pomace in dairy cows does not affect the plasma biochemistry parameters, with the exception of urea concentration, which increased significantly (Chedea et al ., ). Interestingly, due to this diet, the significant higher detected values of β ‐lactoglobulin and lactose give the milk the properties of a functional food, particularly with respect to the biological activities of the former compound.…”
Section: Applicationsmentioning
confidence: 97%